APPLICATION OF RULE OF LAW BY JURISDICTION SYSTEM ON ILLEGAL LOGGING CASE IN INDONESIA 2002-2008 - Permana, Yudistira Hendra (Journal of Indonesian Economy and Business, 2010)
The aim of this research is to analyze behavior of Supreme Courtâs judge on detentionÂ period sentence for illegal logging defendants in Indonesia from year 2002 through 2008.The first analysis is censored normal regression method using detention period indictmentÂ by prosecutor, detention period sentence by district court, defendantâs gender, appealeffort, defendantâs age, and defendantâs job variables. Those variables are used to analyzeÂ how each variable affect on Supreme Courtâs verdict on detention period sentence forillegal logging defendants in Indonesia. Second analysis is descriptive statistic involvesÂ three levels of jurisdictionâs considerations (prosecutor, district court, and SupremeCourt) on determining detention period sentence for illegal logging defendants inÂ Indonesia and suitability those three levels of jurisdiction to law. Researchâs result showsthat detention period indictment by prosecutor, detention period sentence by district court,Â and defendantâs age significantly affect on Supreme Courtâs verdict on detention periodÂ sentence for illegal logging defendants in Indonesia. But, on the other hand there isÂ unsuitable verdict made by those three levels of jurisdiction to law.Keywords: courtâs verdict, illegal logging, censored normal regression